Development of Literature Academic Anxiety From 2002-2021: A Bibliometric Analysis Approach - Azhari, Septian Cahya; Saepulmilah, Ceceng; Meita, Tasya (Lembaga Riset Mutiara Akbar, 2022)
Bibliometric analysis is a statistical tool that is useful for visualizing developments in the field of science to be used as a tool in finding research gaps. This study aims to create a visualization map on the topic of academic anxiety research which includes the development of keywords and popular authors. The database in this study was obtained from dimensions.ai and took data from 2002 to 2021 which was then divided into two ten-year periods. The results of the bibliometric analysis from 2002-2011 contained 6 clusters and 66 keyword items and citation authors with 26 clusters and 59 items. Meanwhile, the results of the bibliometric analysis of the database from 2012-2021 contained 66 items and 8 clusters for popular keywords, while 21 items and 11 clusters for citation authors.